经验、想象与记忆 ： 解严后的台北地景书写 = Experience, memory and imagination : rewriting Taipei landscape in post-martial law era - 陈晞哲 Tan, Xi Zhe (Nanyang Technological University, 2021)
本论文着重在探讨地景书写表层下深刻的历史记忆，生活在土地上的人对“空间”（地景）演变的记述，凿刻的文字是否为移动的“时间”提供了再现和“位移”的魔幻可能, 以较宽广的视角去思考台北地景背后的历史意涵和政治宿命。不同阶段的历史，在台北不同区域留下明显的刻度，不同世代的文学作品释放出强烈的认同色彩。本论文主要以解严后的台北书写为观察点，以关键区域的划分扣连历史重要事件，拆解多元台北被忽略的异质性。 论文剑指台北书写中“逃离”和“遗忘”两大循环不息的主题，其实逃离即是返家，遗忘是因为记忆无处安放。文学台北虽是后殖民城市，但其特殊的身世不同于其他后殖民城市，政治记忆主导话语权。本论文意在跳脱台湾在地学者的二元思维（外省/本省），站在别国的视角审视“中国情结”与“台湾意识”在台北书写中的流动、移转，探索文学作品为地方历史所系的（后）记忆再现，梳理后裔的在地经验和想象空间交织出的认同诉求，观照不同世代对台北意象的临摹。 This thesis focuses on delving deep into the profound historical memory beneath the surface of landscape writing, exploring the possibility of representation and "replacement" of the moving "temporal" through writings of the evolving "space" (landscape) by people living on the land. It reflects on the historical implications and political destiny of the landscape of Taipei from a broader perspective. Different periods in history had left obvious marks in separate areas of Taipei, and literary works of various generations have expressed a strong sense of identity. This thesis focuses on Taipei writings in the post-martial law era as the main subjects of analysis. It divides the city into key areas and links them to important historical events while examining the neglected heterogeneity of a multifaceted Taipei. The thesis identifies the two recurring themes of "escape" and "forgetting" in Taipei writings. To escape is to return home, and one forgets as there is no space for memory. Although literary Taipei is a post-colonial city, its unusual life experience is different from other post-colonial cities. It is a city in which political memory dominates the discourse. This thesis aims to go beyond the binary thinking (Mainlander/Taiwanese) of scholars in China and Taiwan, to examine the flow and shift of "Chineseness" and "Taiwan Consciousness" in Taipei writings from another country’s perspective. It explores the post-memory reflected in the representations of local history in literary works, as well as to study the pursuit for identities that arose from local experience and imaginary space, and analyses the reproduction of the image of Taipei by different generations.